Evidencias de validez y confiabilidad de las escalas de estrés y ansiedad como indicadores de comportamientos desajustados - Palacios Gil, Renzo Ricardo (2025)
The study carried out the necessary analyses to obtain evidence of validity and reliability of the stress and anxiety scales, which belong to the INDACPS. These two indicators are understood as reactions of the organism to adaptation in an environment (stress) or in response to a threat (anxiety). When these reactions are constant and of strong intensity, they tend to manifest themselves in maladjusted behaviors. T he sample comprised 223 adults in Lima, Peru, using non-probabilistic sampling. The type of research was applied technological research of a descriptive-comparative nature. Three models were developed: one unidimensional model where stress and anxiety items were pooled, and two additional models where they were evaluated independently. The exploratory factor analysis for each independent scale showed a single factor for each (stress with a KMO = .837 and anxiety with a KMO = .841), as well as being significant (Bartlett p < .001).